1997
DOI: 10.1152/jn.1997.78.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Activation Lowers the Threshold for NMDA-Receptor-Dependent Homosynaptic Long-Term Depression in the Hippocampus Through Activation of Voltage-Dependent Calcium Channels

Abstract: The effects of the glucocorticoid receptor agonist RU-28362 on homosynaptic long-term depression (LTD) were examined in hippocampal slices obtained from adrenal-intact adult male rats. Field excitatory postsynaptic potentials were evoked by stimulation of the Schaffer collateral/commissural pathway and recorded in stratum radiatum of area CA1. Low-frequency stimulation (LFS) was delivered at LTD threshold (2 bouts of 600 pulses, 1 Hz, at baseline stimulation intensity). LFS of the Schaffer collaterals did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 43 publications
4
47
2
Order By: Relevance
“…By means of selective ligands for the two classes of corticosteroid receptors, namely the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR), it was shown that GRs mediate the aforementioned effects of acute stress on NMDAR-dependent synaptic plasticity in CA1 (Xu et al, 1998;Yang et al, 2004). This conclusion is in keeping with the respective properties of MRs and GRs to be activated by low and high concentrations of corticosterone [such as those reached during stress (De Kloet, 1991)] and the observation in control slices that GR stimulation by exogenous agonists or by high corticosterone concentrations impedes synaptic potentiation while it enhances LTD in CA1 (Diamond et al, 1992;Coussens et al, 1997;Alfarez et al, 2002;Wiegert et al, 2005). Together, these data clearly indicate that stress, through corticosterone release, is endowed with metaplastic properties (Kim and Diamond, 2002).…”
Section: Introductionsupporting
confidence: 77%
“…By means of selective ligands for the two classes of corticosteroid receptors, namely the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR), it was shown that GRs mediate the aforementioned effects of acute stress on NMDAR-dependent synaptic plasticity in CA1 (Xu et al, 1998;Yang et al, 2004). This conclusion is in keeping with the respective properties of MRs and GRs to be activated by low and high concentrations of corticosterone [such as those reached during stress (De Kloet, 1991)] and the observation in control slices that GR stimulation by exogenous agonists or by high corticosterone concentrations impedes synaptic potentiation while it enhances LTD in CA1 (Diamond et al, 1992;Coussens et al, 1997;Alfarez et al, 2002;Wiegert et al, 2005). Together, these data clearly indicate that stress, through corticosterone release, is endowed with metaplastic properties (Kim and Diamond, 2002).…”
Section: Introductionsupporting
confidence: 77%
“…Furthermore, several studies have shown that glucocorticoids are able to activate NMDA receptors by different direct and indirect mechanisms, including activation of voltage-dependent calcium channels or modulation of calcium influx (Kim et al, 1996;Coussens et al, 1997). The potential implication of these mechanisms in the present model remains to be determined.…”
Section: Ionotropic Glutamate Receptor Expressionmentioning
confidence: 88%
“…These findings are consistent with known GR actions within the CNS. For example, activation of central GR has been associated with (1) NMDAR-dependent long-term depression (Coussens et al, 1997) and an elevated intracellular Ca 2ϩ concentration in hippocampal neurons (Takahashi et al, 2002), (2) modulation of the NMDAR function (Nair et al, 1998), (3) the potentiated response to NMDA of dopamine-sensitive neurons in the ventral tegmental area (Cho and Little, 1999), (4) neuronal apoptosis mediated through intracellular mitogen-activated protein kinases (Diem et al, 2003), and (5) inhibition of bradykinininduced Ca 2ϩ influx via PKC activation (Qiu et al, 2003). Thus, the role of GR in spinal NR1 and PKC␥ expression is indicative of a broad cellular mechanism of GR regulation under various conditions, including chronic morphine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the NMDAR-mediated response to excitatory amino acids of dopamine-sensitive neurons within the ventral tegmental area can be potentiated by GR activation (Cho and Little, 1999). Central GR also plays a role in NMDAR-mediated long-term depression (Coussens et al, 1997) and the regulation of NMDAR-and GR-mediated neuronal degeneration (Abraham et al, 2000;Lu et al, 2003). Indeed, periph-eral nerve injury has been shown to upregulate spinal GR followed by a downstream upregulation and functional modulation of NMDAR (Wang et al, 2004(Wang et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%